Normal Closure Behavior of Rock Fractures Considering Transition from Elastic Deformation to Fully Plastic Flow - Huang, Lin; Zhao, Cheng; Li, Bo; Mo, Yangyang; Xing, Jinquan; Chen, Huiguan (Rock mechanics and rock engineering, 2023)
Highlights A rock fracture closure analysis considering the transition from elastic deformation to fully plastic flow is established. The contact analysis incorporating the transition regime is more effective and precise in modeling rock fracture closure. Neglecting the transition regime underestimates the fracture closure and damaged area and overestimates the fracture stiffness.